Visualizing cityscapes of classical antiquity : from early modern reconstruction drawings to digital 3D models : with a case study from the ancient town of Koroneia in Boeotia, Greece - Piccoli, Chiara (Archaeopress Publishing Ltd, 2018)
The study presented here makes a practical contribution to a new understanding and use of digital 3D reconstructions in archaeology, namely as 'laboratories' to test hypotheses and visualise, evaluate and discuss multiple interpretations.